2018
DOI: 10.1051/0004-6361/201833711
|View full text |Cite
|
Sign up to set email alerts
|

Supercluster A2142 and collapse in action: infalling and merging groups and galaxy transformations

Abstract: Context. Superclusters with collapsing cores represent dynamically evolving environments for galaxies, galaxy groups, and clusters. Aims. We study the dynamical state and properties of galaxies and groups in the supercluster SCl A2142 that has a collapsing core, to understand its possible formation and evolution. Methods. We find the substructure of galaxy groups using normal mixture modelling. We have used the projected phase space (PPS) diagram, spherical collapse model, clustercentric distances, and magnitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 131 publications
5
46
0
Order By: Relevance
“…The tail as a whole resembles the thick filament described in Cautun et al (2013). Earlier studies have shown that the supercluster main body is already collapsing or will collapse in the future (Einasto et al 2015;Gramann et al 2015;Einasto et al 2018c).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…The tail as a whole resembles the thick filament described in Cautun et al (2013). Earlier studies have shown that the supercluster main body is already collapsing or will collapse in the future (Einasto et al 2015;Gramann et al 2015;Einasto et al 2018c).…”
Section: Introductionmentioning
confidence: 69%
“…Nine such groups lie in the HDC of the supercluster, and 12 lie at the supercluster axis along an almost straight line. These groups in the supercluster, their galaxy content, and dynamical state were analysed in Einasto et al (2018c). We highlight groups with at least ten galaxies in the cocoon to compare the properties of groups in both environments.…”
Section: Filaments and Groups In The Supercluster And In The Cocoonmentioning
confidence: 99%
See 3 more Smart Citations